PER ORAL INOCULATION OF LYSINIBACILLUS SPHAERICUS WITH PATHOGENIC MIBROBES ON REARING AND COCOON PARAMETERS OF SILKWORM, Bombyx mori L. - H. G. ANUSHA,; R. N. BHASKAR; K. V. ANITHARANI (The Bioscan, 2020)
Mixed infections are complex interactions between pathogens and silkworm which cause diseases and reduces cocoon crop loss. The per oral inoculation of pathogenic bacterium Lysinibacillus sphaericus along with viz., A. faecalis (A), B. subtilis (B) and NPV (N) to third instar PM×CSR 2 (50 silkworms/ replication) resulted minimum of 7.87 and 9.85 days for ET 50 symptom expression and mortality in treatment T 6 - L. sphaericus + A. faecalis +NPV. The remaining treatments T 5 triple inoculation (L+A+B) (9.89 and 12.36 days) and dual inoculation T 2 (L+A) (20.89 and 23.29 days ) ,T 3 (L+B) (10.10 and 12.48 days ) and T 4 (L+N) (10.18 and 11.18 days) recorded different days for symptom expression and mortality. Further, number of larvae entered to fourth instar was noticed minimum in T 6 -L. sphaericus + A. faecalis + NPV (30) and maximum in T 2 -L. sphaericus + A. faecalis (44). Further, the cocoon parameters viz., single cocoon weight (1.00 g), shell weight (0.08 g), shell ratio (8.00) and silk productivity (0.69 cg/ day) was noticed minimum in T6. The interaction effect of Lysinibacillus sphaericus with other pathogenic bacteria viz.,Bacillus subtilis, Alcaligenes faecalis and NPV had synergistic effect compared to Lysinibacillus sphaericus alone.